The past futures of techno-scientific promises. (26th August 2021) - Joly, Pierre-Benoit; Le Renard, Claire
Abstract: Previous studies have shown that techno-scientific promises play key roles in the process of emergence of new technologies. The role of promises in the emergence of old technologies when they were young has, however, been overlooked. The main objective of this paper is to fill this gap. We draw on the concept of 'regime of historicity', defined as an organizational structure given societies impose on the experience of time and articulate the present, the past, and the future. Using four case studies, we argue that the way techno-scientific promises align with regimes of historicity is crucial. This paper shows that promising in the presentist regime using the modernist frame of innovation (creative destruction) raises many problems Instead, the building of horizons of hope may rest on promises based on processes of collective experimentation.